Ukrainian agriculture during the full-scale Russian-Ukrainian war: consequences, policy responses and recovery strategies - Maryna Nehrey; Nataliia Klymenko; Volodymyr Kravchenko; Mariana Komar (Agricultural and Resource Economics)
Purpose. The present paper examines the impact of the full-scale Russian-Ukrainian war (RUW) on Ukraine’s agricultural sector, focusing on the period from 24 February 2022 to the end of 2024. The article has three objectives: firstly, to assess the extent of losses in agriculture; secondly, to evaluate government policy measures; and thirdly, to propose strategies for post-war recovery.